The Phoenix and the Carpet - Nesbit, E. (Edith), 1858-1924 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Phoenix and the Carpet" by E. Nesbit is a fantasy novel published in 1904. When five siblings accidentally destroy their nursery carpet with fireworks, their parents buy a replacement that contains a mysterious glowing egg. The egg hatches into a talking Phoenix, who reveals the carpet is magical and can grant three wishes daily. The children embark on exotic adventures across time and space, accompanied by their vain and eccentric feathered companion, though their magical gifts prove more fragile than expected. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Phoenix_and_the_Carpet
Release date is 1997-03-01
Produced by Jo Churcher, and David Widger
Keywords: Fantasy fiction; Siblings -- Juvenile fiction; Magic -- Juvenile fiction; Great Britain -- History -- Edward VII, 1901-1910 -- Juvenile fiction; Phoenix (Mythical bird) -- Juvenile fiction